iPSC-Derived Organoids as Therapeutic Models in Regenerative Medicine and Oncology - Turhan, Ali G.; Hwang, Jinwook W.; Chaker, Diana; Tasteyre, Albert; Latsis, Theodoros; Griscelli, Frank; Desterke, Christophe; Bennaceur-Griscelli, Annelise (Frontiers in Medicine, 2021)
Progress made during the last decade in stem cell biology allows currently an unprecedented potential to translate these advances into the clinical applications and to shape the future of regenerative medicine. Organoid technology is amongst these major developments, derived from primary tissues or more recently, from induced pluripotent stem cells (iPSC). The use of iPSC technology offers the possibility of cancer modeling especially in hereditary cancers with germline oncogenic mutations. Similarly, it has the advantage to be amenable to genome editing with introduction of specific oncogenic alterations using CRISPR-mediated gene editing. In the field of regenerative medicine, iPSC-derived organoids hold promise for the generation of future advanced therapeutic medicinal products (ATMP) for organ repair. Finally, it appears that they can be of highly useful experimental tools to determine cell targets of SARS-Cov-2 infections allowing to test anti-Covid drugs. Thus, with the possibilities of genomic editing and the development of new protocols for differentiation towards functional tissues, it is expected that iPSC-derived organoid technology will represent also a therapeutic tool in all areas of medicine.